2008
DOI: 10.1146/annurev.pharmtox.48.121806.154910
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin: Therapeutic Potential of an Early Sensor of Carcinogenic Transformation

Abstract: The avian virus-derived protein apoptin induces p53-independent apoptosis in a tumor-specific way. Apoptin acts as a multimeric complex and forms superstructures upon binding to DNA. In tumor cells, apoptin is phosphorylated and mainly nuclear, whereas in normal cells it is unphosphorylated, cytoplasmic, and becomes readily neutralized. Interestingly, apoptin phosphorylation, nuclear translocation, and apoptosis can transiently be induced in normal cells by cotransfecting SV40 large T oncogene, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 98 publications
1
79
0
Order By: Relevance
“…Apoptin is a viral protein from the chicken anemia virus (CAV) which is able to induce apoptosis in tumor cells. This protein, with a molecular weight of 13,600 Da, is composed of 121 amino acids and contains 2 functional regions (13). In previous studies, the following merits of Apoptin in antitumor therapy were revealed: Apoptin is able to induce apoptosis in numerous types of malignant tumor cells (13); Apoptin is capable of killing tumor cells but not normal cells (4); Apoptin is able to induce high levels of apoptosis in tumor cells (14); the antitumor effect of Apoptin does not depend on the expression of p53 (15); Apoptin is able to induce high levels of apoptosis in tumor cells expressing the anti-apoptosis proteins Bcl-2 and Bcl-xL (16).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptin is a viral protein from the chicken anemia virus (CAV) which is able to induce apoptosis in tumor cells. This protein, with a molecular weight of 13,600 Da, is composed of 121 amino acids and contains 2 functional regions (13). In previous studies, the following merits of Apoptin in antitumor therapy were revealed: Apoptin is able to induce apoptosis in numerous types of malignant tumor cells (13); Apoptin is capable of killing tumor cells but not normal cells (4); Apoptin is able to induce high levels of apoptosis in tumor cells (14); the antitumor effect of Apoptin does not depend on the expression of p53 (15); Apoptin is able to induce high levels of apoptosis in tumor cells expressing the anti-apoptosis proteins Bcl-2 and Bcl-xL (16).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptin has been reported to induce the selective death of tumor cells derived from diverse tumors, whereas it does not induce apoptosis in nontransformed cells (3,48,59). The manner by which apoptin distinguishes between tumor and normal cells remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptin is a small viral protein that was originally identified in chicken anemia virus and shows remarkable anticancer toxicity and selectivity (3,48,59). The tumor-selective cell death induced by apoptin has been demonstrated in a great number of tumor cells of different origins by the use of several techniques, including overexpression or introduction of cell-permeative apoptin constructs (8,13,24,51).…”
mentioning
confidence: 99%
“…as protein or gene therapy. In any case, efficient systems are required to facilitate the delivery of apoptin to cancer cells or expression of apoptin within these cells [26][27][28][29][30] . The HIV TAT transduction domain has been successfully used to deliver apoptin into cancer cells [14] , and no apoptosis of normal cells (HUVECs) was observed with this TATapoptin fusion protein.…”
Section: Discussionmentioning
confidence: 99%